The Weightiness of a Blank - Iman Mirza (Penerbit UTHM, 2025)
Sometimes the heart breaks and cries; sometimes the heart mends and reposes; at times the heart goes cold in bewilderment; thank God most of the time the heart keeps warm and carries on. 30 poems written over 2 cycles of Ramadhan: Unwinding the heart’s musical box and projecting imagery from dancing words. Without the faintest idea of dramatization and sensationalisation, speaking truths as truths reflect themselves in the most unbiased mirror called conscience: A blank space open for interpretation. Would you care to spare 30 minutes to fill this BLANK?